TRANSFORMASI METODE PENDIDIKAN BUDDHIS GLOBAL: STUDI PERBANDINGAN ANTARA KULIKULUM FO GUANG SHAN DAN STABN RADEN WIJAYA - Saputra , Dita; Darma, Widia; Suyatno, Tri (Inisiasi, 2025)
This study compares the Buddhist curriculum and education methods between Fo Guang Shan which is global and modern in style and the local and structured Raden Wijaya State STAB. The problem arises from significant differences in the approach of the two to Buddhist education. The purpose of the study was to analyze these differences to understand their implications for the spread of Buddhism. The method used is a literature study by examining books, journals, reports, and relevant literature. The data was analyzed using content analysis techniques. The results show that Fo Guang Shan emphasizes innovation and multiculturalism, while STAB prioritizes national regulations and local wisdom. The conclusion confirms that Buddhist education is able to transform according to the social context, as well as offering a framework for curriculum development that is adaptive and balanced between a global orientation and the preservation of local values.